Quilombo urbano liberdade, patrimônio afro de São Luís-MA: a sistemática da acessibilidade aos direitos culturais à luz da constituição federal de 1988 e do estatuto da igualdade racial - SILVA, Mariana Queen Cardoso da (2023)
This research addresses the way (s) in which residents have access to cultural rights in the Quilombo Urbano Liberdade in São Luís - MA, as an expressive Afro Heritage in the light of the 1988 Federal Constitution and the Statute of Racial Equality. This is a bibliographical, exploratory, interdisciplinary field study, which dialogues with areas such as Law, History and Cultural Heritage, with documentary, bibliographical and field research, with records of the space to be investigated, as well as its cultural and religious manifestations. We worked with the categories of quilombos and urban quilombo, culture, cultural heritage, memory, from the perspective of authors such as Robin Blackburn (2003), Armitage (2004), Grosfoguel (2010), Almeida (1996), Alexandre Marcussi (2012), Reis (1996), Gomes (1996), Clóvis Moura (1959), Carril (2006), ,Arruti (2003), Cardoso (2005), ), Mundinha Araújo (2008), Santos (2013), Halbawchs (2006), Márcia Chuva (2006), Lilian Schwarcz (2011), Stuart Hall (2013), Cunha Júnior (2014, 2019) and Homi Bhabha (1998). However, cultural rights are studied from the perspective of the author Humberto Cunha Filho and are later related to the cultural right provided for in the Statute of Racial Equality - Law No. 12. 288/2010. After these theoretical studies, the cultural reality of the Quilombo Urbano Liberdade in São Luís-MA is related, rescuing the history of its urban formation in the city of Ludovic, where it is largely related to its Afro-Brazilian and cultural identity of the quilombola community. It is concluded that its historical formation plays a fundamental role in the continuation of the identity process, which translates into the protection of its cultural rights. As for the research carried out with some cultural producers, we also found that there are difficulties in accessing cultural notices, as well as the legal insecurity that these cultural notices pose to cultural producers. In addition, these cultural notices need to generate a greater concentration of income and employment for cultural producers, considering that they live from their culture, because in the Quilombo Urbano da Liberdade, cultural and economic rights are largely related, since cultural producers use their cultural manifestations to preserve their ancestry and cultural identity and also to generate employment and income.